Taxonomic revision of the Square-tailed Drongo species complex (Passeriformes: Dicruridae) with description of a new species from western Africa - Fuchs, Jérôme; Douno, Mory; Bowie, Rauri C.k.; Fjeldså, Jon (Zootaxa, 2018)
We describe a new species of drongo in the Square-tailed Drongo (Dicrurus ludwigii) complex using a combination of biometric and genetic data. The new species differs from previously described taxa in the Square-tailed Drongo complex by possessing a significantly heavier bill and via substantial genetic divergence (6.7%) from its sister-species D. sharpei. The new species is distributed across the gallery forests of coastal Guinea, extending to the Niger and Benue Rivers of Nigeria. We suspect that this taxon was overlooked by previous avian systematists because they either lacked comparative material from western Africa or because the key diagnostic morphological character (bill characteristics) was not measured. We provide an updated taxonomy of the Square-tailed Drongo species complex.